AB203. A randomized trial of trigone-including versus trigone-excluding intradetrusor injection of BTX-A for decreasing detrusor leak point pressure in patients with urinary incontinence secondary to spinal cord injury in China - Hui, Chen (Transl Androl Urol, 2016)
OBJECTIVE: To compare the safety and efficacy of trigone-including versus trigone-excluding intradetrusor injection of botulinum toxin A (BTX-A) for decreasing detrusor leak point pressure (DLPP) in patients with urinary incontinence (UI) secondary to spinal cord injury (SCI) in China. METHODS: A prospective, multicenter, single-blind and randomized controlled trial (RCT) was conducted between December 2012 and June 2015. Patients with UI and low compliance bladder secondary to SCI were recruited. At a 1:1 ratio, patients randomly received 200 U BTX-A intradetrusor injections excluding the trigone (control group) or 160 U intradetrusor and 40 U intratrigonal injections (experimental group). Patients were evaluated at baseline, and 4, 12 weeks after injection. The efficacy and safety outcomes included DLPP, detrusor leak point volume (LPV), I-QoL, voiding volume, UI episodes, complete dryness. Vesicoureteral reflux (VUR) and other adverse events were recorded. RESULTS: Eighty-six patients were recruited and 80 (41 in experimental group and 39 in the control group) of them completed the trial. There were no significant differences in baseline evaluation items (gender, age, duration of SCI, level of neurological injury, AIS scores) between the two groups. At 12 weeks, the improvement was significantly better in the experimental group than in the control group for DLPP (−25.66 vs. −19.70 cmH(2)O, P=0.02), DLPV (116.09 vs. 87.34 mL, P=0.03), I-QoL (27.02 vs. 20.32, P=0.02), mean UI episodes (−7.19/d vs. −6.65/d, P=0.01), complete dryness (22 vs. 10, P=0.01),mean voiding volume (142.84 vs. 110.36 mL, P=0.01). In both of two groups, no patients developed VUR. CONCLUSIONS: Trigone-including intradetrusor injection of BTX-A are more effective than those excluding the trigone to decrease DLPP for patients with UI and poor compliant bladders secondary to SCI. It does not induce VUR.